Identification of Differently Expressed Genes Associated With Prognosis and Growth in Colon Adenocarcinoma Based on Integrated Bioinformatics Analysis - Hu, Ming; Fu, Xiandong; Si, Zhaoming; Li, Chunming; Sun, Jihu; Du, Xinna; Zhang, Hu (Frontiers in Genetics, 2019)
Latest statistics showed that the morbidity and mortality of colon adenocarcinoma (COAD) ranked fourth and fifth, respectively, around the world. COAD was a heterogeneous disease, and the high rates of recurrence, metastasis, and drug resistance still posed great challenges for treatment, which needs to further develop therapeutic and prognostic targets. In this study, we got the top 3,075 differentially expressed genes (DEGs) and 1,613 potential prognostic genes by GEPIA 2 and identified 1,166 fitness genes in COAD based on genome-scale CRISPR-Cas9 knockout (GeCKO) screening data. Excluding the genes already reported in the literatures, a total of nine DEGs overlapping with prognostic and fitness genes were further analyzed. High expression of CCT6A, RHOQ, and RRP12 promoted COAD cell growth and were relative to lower survival rate of COAD patients, while high expression of UTP18, DDOST, YRDC, ACTG1, RFT1, and NLE1 also promoted COAD cell growth, but were relative to higher survival rate. In addition, CCT6A, UTP18, YRDC, RRP12, RFT1, NLE1, as well as DDOST were essential genes across pan-cancer including COAD cells, and ACTG1 and RHOQ were less essential genes in cancer cells. In a word, we discovered nine novel potential genes that could serve as anticancer targets and prognostic markers in COAD and its subtypes.